Whole Exome Sequencing Revealing RYR1 Pathogenic Variant in an Exceptional Family with Malignant Hyperthermia Susceptibility - Khongkraparn A. (2023)
Objective: To use whole exome sequencing (WES) in identifying pathogenic allele(s) in a challenging family of which specimen of the malignant hyperthermia (MH)-suspected case was not available. Points related to genetic counseling were also discussed. Materials and Methods: A counselee walked in for genetic counseling and genetic test as there was a "deadly allergic reaction to anesthesia" in one of the family relatives. Multiple sessions of pre-test counseling were provided to the whole family. WES with targeted analysis of 23 genes associated with malignant hyperthermia susceptibility was carried out in nine individuals including one of the adult children, full sibs, and half-sib of the index case. Fourteen computational prediction programs, which included REVEL, DANN, DEOGEN2, FATHMM-MKL, LIST-S2, M-CAP, MVP, PolyPhen2, MutationTaster, BayesDel_addAF, EIGEN, MutationAssessor, PrimateAI, and SIFT, were used for pathogenicity prediction. Results: The family consisted of 4-generation pedigree and comprised of 36 blood-related individuals. The authors identified two RYR1 variants, c.550G>A (p.Ala184Thr) and c.1840C>T (p.Arg614Cys). The inferred genotype was heterozygous p.Arg614Cys for the index case and compound heterozygous p.Ala184Thr/p.Arg614Cys for the father of the individual. The p.Arg614Cys allele was previously proved to be pathogenic. Therefore, the p.Ala184Thr, which was not present in Thai reference genomes, was concluded to be non-pathogenic. Five additional family members were found to carry the RYR1 pathogenic variant and were given comprehensive post-test counseling. Conclusion: WES analysis is a powerful tool for determining the pathogenic allele in MH susceptibility family, even in the absence of specimen of the index case. However, comprehensive pre- A nd post-test genetic counseling and careful selection of the individuals to be tested is mandatory.